Odpowiedzi

2010-02-15T13:09:00+01:00
A) 3x+y=3
2x-3y=2

y=3-3x
2x-3(3-3x)=2

2x-9+9x=2

11x=11

x=1

y=3-3x = 3-3*1 = 3-3 = 0

b) [-3x+2y=-7
klamra -> [5x+2y=1

3x-2y=7
5x+2y=1

8x=8
x=1

3x-2y=7
3*1-2y=7
-4=2y
y=-2
2 5 2
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-15T13:09:44+01:00
A) 3x+y=3
2x-3y=2

y=3-3x
2x-3(3-3x)=2

2x-9+9x=2

11x=11

x=1

y=3-3x = 3-3*1 = 3-3 = 0

b) [-3x+2y=-7
klamra -> [5x+2y=1

3x-2y=7
5x+2y=1

8x=8
x=1

3x-2y=7
3*1-2y=7
-4=2y
y=-2



1 5 1
2010-02-15T13:10:55+01:00
A) 3x+y=3/3
2x-3y=2

9x+3y=9
2x-3y=2
------------
+
11x=11/11
x=1

3+y=3
y=0
x=1

spr.3+0=3

b) -3x+2y=-7/-1
5x+2y=1
3x-2y=7
5x+2y=1
----------
+
8x=8/8
x=1
5+2y=1
2y=-4/2
y=-2
x=1

spr.5-4=1
1 1 1